Питання інформаційного протистояння в умовах інформаційної війни - Заскальна, Анна; Білущак, Тетяна (Видавництво Львівської політехніки, 2017)
The article dwells on such complex notions as information space and information security, touching upon respective problems Ukraine is experiencing in the area.
Keywords: інформація; медіавакцинація; інформаційна безпека; інформаційний імунітет; медіапроцес